Biological control of anthracnose (Colletotrichum gloeosporioides) and high-quality walnut production in walnut (Juglans regia L.) trees by Bacillus licheniformis PR2 - Jae-Hyun Moon; Sang-Jae Won; Vantha Choub; Su-In Choi; Ju-Yeol Yun; Henry B. Ajuna; Young Sang Ahn (Biological Control)
Walnut (Juglans regia L., Fam.: Juglandaceae) is an economically important crop worldwide, but its production is hampered by notorious diseases such as walnut anthracnose caused by Colletotrichum gloeosporioides. This study aims to demonstrate the potential of Bacillus licheniformis PR2 as an alternative to chemical fungicides through the production of bioactive enzymes which degrade the phytopathogenic fungal cell walls to inhibit its mycelial growth and spore germination and consequently suppress anthracnose disease. The study further demonstrates the potential of PR2 to improve the yield and quality of walnut kernels through phytohormone production and improving nutrient availability in soil. During its growth in the bacterial culture, PR2 exhibited strong antifungal potential by producing cell wall degrading enzymes such as chitinase, β-1,3-glucanase and protease which degraded the cell wall chitin, β-glucans and glycoproteins polymers of C. gloeosporioides. The crude enzyme fraction of PR2 at 100 µL/mL inhibited spore germination and mycelial growth of C. gloeosporioides by 89.22 % and 33.31 %, respectively. Field application of PR2 culture resulted in 3.60-fold and 3.47-fold reduction of anthracnose disease incidence compared to the conventional treatment and control groups, respectively. For the growth-promoting properties, PR2 produced indole-3-acetic acid (IAA), a phytohormone known to enhance root development up to 148.49 mg/mL during growth and demonstrated the potential for phosphate-solubilization and ammonium-nitrogen production, thereby increasing the availability of essential nutrients in the soil. Application of PR2 in the field elevated the concentration of nitrogen and available phosphorus by 1.70-fold and by 1.56-fold compared to the conventional treatment and control group, respectively. Inoculation of PR2 also elevated the concentration of available phosphate in the rhizosphere by 2.57-fold and 2.67-fold compared to the conventional treatment and control group, respectively. These growth-promoting properties improved the uptake of essential nutrients by walnut plants and resulted in higher chlorophyll content/photosynthetic capacity in walnut leaves, which in turn resulted in higher yield and improved physical characteristics of walnut kernels, such as the average kernel length, diameter, weight and firmness. Moreover, the inoculation of PR2 in walnut field increased calcium uptake and content in walnut kernel by promoting calcium solubilization from metal complexes through organic acid production (lowering soil pH) and the increased Ca content improved kernel firmness by reinforcing the pellicle cell walls. These findings demonstrate that B. licheniformis PR2 has dual potential to directly inhibit phytopathogenic infections through enzymatic degradation of the fungal cell walls while simultaneously inducing beneficial physiological processes to improve walnut yield and kernel quality. Therefore, B. licheniformis PR2 could potentially be applied as an eco-friendly alternative to chemical fungicides and fertilizers for sustainable disease control and improving the production of high-quality walnut kernels.